Views of Nursing Students Conducting the Virtual Reality Application of Tracheostomy Care Based Gaming - Bayram, Sule Biyik; Caliskan, Nurcan (University of Pardubice, 2018)
Introduction: Game-based virtual reality application is a simulation method in which a real life situation is gamified after being transferred to a computer environment. Aim: The aim of this study is to find out the opinions of nursing students who used the game-based virtual reality application for tracheostomy care. Method: The study consisted of 43 students that were enrolled in the Fundamentals of Nursing course in the spring term of the 2016–2017 academic year. First of all, a video file was made according to the steps of tracheostomy care and a scenario for the game-based virtual reality application was written. The game was installed on the mobile phones of students who participated in the theoretical course of tracheostomy care, completed the practice and agreed to participate in the study. Students were instructed on how to play the game and were told to play the game for a week. At the end of the week, students were told to share their opinions on the game. Numbers, percentages, means and standard deviation were used as descriptive statistical methods while evaluating the data. Results: The three positive statements about the use of the application were that “the information in the application was legible” (4.37 ± 0.78), “the game could be completed without any problems”, (4.86 ± 0.63), and “the steps of the process were able to be carried out” (4.72 ± 0.70). Conclusion: It is proposed that the game-based virtual reality application can be used for the teaching of tracheostomy care, which requires the implementation of the principles of surgical asepsis, it is complex, hard to visualize and to be learned by students and less likely to be encountered in clinics, in nursing education.
Keywords: game based virtual reality; nursing student; tracheostomy care